Evaluation of new polar functionalised sol-gel hybrid sorbent for stir bar sorptive - Abu Bakar, Nur Atiqah (2014)
Stir bar sorptive extraction is widely used in the extraction of analytes from aqueous samples. However, commercial stir bar is relatively expensive. The high cost of the stir bar has led to the development of new coatings mainly based on silica. In this study, a new organic-inorganic hybrid silica-based material based on 3-mercapto-propyltrimethoxysilane (MPTMOS) and methyltrimethoxysilane (MTMOS) was synthesized via sol-gel technology and use in the evaluation of its extraction performance of three organic dyes namely crystal violet, methylene blue and methyl orange as test analytes. The test analytes were analyzed simultaneously using UV-Vis spectroscopy at 422 nm for methyl orange, 592 nm for crystal violet and 653 nm for methylene blue. Several sol-gel preparation parameters were optimized to obtain the sorbent with optimum extraction efficiency for the three selected dyes. The organic-inorganic sol-gel hybrid sorbent with the composition 3:1 MPTMOS-MTMOS showed the highest extraction performance for the three selected dyes.